The rise of forestry in the United States - Jones, John Seneca (My University, 1908)
Introduction: From a time practically contemporaneous with the first colonial settlements the problem of forest economics has been recognized and debated in the United States. The first colonial settlements were formed of men of almost every trade and profession, and it was then and there that they struck off into the forests from which they were to hew out their homes.
Citation: Jones, John Seneca. The rise of forestry in the United States. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Forests; Forestry; Trees; Legislation; Graduating theses; Senior theses; Theses